IMPACT OF PLANT GROWTH INHIBITORS ON THE GROWTH AND YIELD OF SORGHUM - Abood, N. M.; SHALAL, E. M.; HAMDAN, M. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Field experiment was carried out during the spring and fall seasons of 2019 at the Abu Ghraib Research Station of the Agricultural Research Office/ Ministry of Agriculture, was aimed to investigate the effect of plant growth inhibitors on growth and yield of several sorghum varieties .Randomized Complete Block Design within split plot arrangement with three replications was used. The main plot consists of three growth inhibitors (Cycocel, Ethiphon, and Mebiquat), which were added at stages six and eight leaf stage, in addition to the control treatment (distilled water only), the sub plot was included three cultivars (Mabrouk, Buhooth 70 and Giza 113). The results showed in both seasons significant interaction between cultivars and growth inhibitors in most of the studied traits. The plants of the variety Giza 113 sprayed with Ethiphon recorded the lowest period of reaching physiological maturity, the highest average dry matter yield, and the highest weight of 1000 grains (89.00 days, 17.32 ton ha-1, and 39.33 gm) respectively. The same variety recorded the highest content of chlorophyll in the leaves and the highest grain yield due to the effect of Mebiquat (49.50 spad, 3.93 ton ha-1. The cultivar Buhooth 70 with the effect of Cycocel achieved the highest average of dry matter yield of 33.27 ton ha-1.